The Effect of Learning Strategy, Stress Management, and Social Support on Student Productivity: A Human Resource Development Perspective among FEBI UINSU Students - Ridho Alfi Fajar Hidayat; Tri Inda Fadhila Rahma; Nurbaiti Nurbaiti (Journal Development Manecos, 2026)
This study aims to analyze the influence of learning strategy, stress management, and social support on student productivity among students of the Faculty of Islamic Economics and Business at Universitas Islam Negeri Sumatera Utara. This research employs a quantitative approach with an explanatory research design involving 100 respondents selected through proportionate stratified random sampling. Data analysis was conducted using multiple linear regression with the assistance of IBM SPSS Statistics. The results indicate that learning strategy does not have a significant effect on student productivity, while stress management and social support have a positive and significant influence in improving productivity. Simultaneously, all three variables have a strong effect on student productivity, highlighting the importance of integrating cognitive, psychological, and social aspects in supporting academic performance. The main finding of this study reveals that social support is the most dominant factor, indicating that support from the surrounding environment, such as family, peers, and institutions, plays a greater role compared to other factors in enhancing student productivity. The novelty of this study lies in its integrative approach, which combines these three aspects simultaneously within the context of Islamic higher education, which has previously been examined in a more partial manner.